Student satisfaction in higher education: a portuguese case study - Marie, Caterina de (2018)
The competition has increased pressure on public institutions to offer consistent quality service to retain students as well as to recruit new students. Hence, higher education providers should be aware of students’ expectations and implement strategies to oriented for these expectations and exceed the same. The student satisfaction assessment is crucial in determining service quality at higher education institutions. In this regards, this research attempts to measures the level of student satisfaction who attend the School of Technology and Management of Bragança (ESTiG) with the Polytechnic Institute of Bragança (IPB) -Portugal-, during the academic year 2013/2014. A survey was conducted to collect the data involved a sample of 220 students from Business and Technologies scientific area. The results showed that ESTiG students were generally satisfied with IPB. There is a significant correlation among all items with Student Overall Satisfaction. It was identified two satisfaction determinants: ‘Quality Service’ and ‘Loyalty’. By the results produced with multiple regression, it was achieved that the Loyalty is the variable with high influence on the Student Overall Satisfaction. Loyalty and Quality Service explain 99.7% Student Satisfaction. The results of this research study will help the main board of the IPB and ESTiG in understanding the changing needs of students during the educational process.